Elective hand surgery and concomitant corticosteroid injection: Confirming increased infection risk using A national dataset - Benjamin J. Kirby; Jashvant Poeran; Nicole Zubizarreta; Daniel A. London (Surgery in Practice and Science)
Background: Recent studies demonstrate a link between corticosteroid injection and surgical complications when procedures occur shortly after steroid administration. These publications focus on single procedures like carpal tunnel release. This study seeks to demonstrate how surgical site infection risk changes across thirteen common elective hand procedures when steroid injection is performed contemporaneously. Methods: The Truven MarketScan® database identified patients who had undergone elective hand surgery between 2015 and 2016. Two cohorts were created based on the administration, or absence thereof, of contemporaneous corticosteroid injection. The primary outcome measure was infection within 30 days of surgery as measured by antibiotic prescription or repeat surgical intervention. Multivariate logistic regression was performed to assess the association between concomitant corticosteroid injections and post-operative infections while controlling for demographics and comorbidities. Results: 149,689 patients underwent elective hand surgery. 6104 (4.1 %) received concomitant corticosteroid injection and 14,070 (9.4 %) received post-operative antibiotics or underwent secondary surgical intervention for infection. Treatment for post-operative infection was significantly higher in the corticosteroid group (10.2 % versus 9.3 %; p = 0.02) driven by difference in severe infection requiring surgical intervention (3.7 % versus 3.1 %; p = 0.03). This finding persisted when controlling for demographics and comorbidities with adjusted OR of 1.10 (CI 1.01–1.20) for all infections and 1.16 (CI 1.01–1.33) for severe infections. Discussion: These results support prior findings that patients undergoing concurrent steroid injections and surgery have increased rates of infectious complications though the absolute risk remains small. Limitations of the database preclude further investigation into the details of each procedure (e.g. ipsilateral vs contralateral injection, peri-operative antibiotics) which may impact infection rates. Conclusions: Concomitant steroid injection with elective hand surgery may increase the risk of postoperative infection, particularly severe infection. However, that relative increase lies between 1 and 33 percent and should be weighed against the benefit from intraoperative corticosteroid administration.